The Notebook of Dhutmose The Notebook of Dhutmose - Regina Hölzl; Michael Neumann; Robert J. Demarée (Probleme der Ägyptologie, 2018)
In The Notebook of Dhutmose Regina Hölzl, Michael Neumann and Robert Demarée document the surprising discovery and the contents of a papyrus scroll found in an ibis mummy jar in the Kunsthistorisch Museum in Vienna. The twenty-four columns of text constitute a unique notebook of the Scribe Dhutmose who is well-known as the author of administrative documents and a private correspondence. He was active as chief administrator of the institution responsible for the creation of royal tombs in Western Thebes at the end of the Ramesside Period, around 1100 BCE. The texts concern financial accounts relating to the acquisition of copper tools and weapons, but also private affairs like an inventory of his amulets and jewelry and a report about the robbery of his personal belongings.